Multicenter Cross-Sectional Study on Perceptions and Roles of Community Pharmacists in the Prevention and Management of Cardiovascular Disorders in Northwest Ethiopia - Sendekie AK; Netere AK (Dove Medical Press, 2022)
Ashenafi Kibret Sendekie, Adeladlew Kassie Netere Department of Clinical Pharmacy, School of Pharmacy, College of Medicine and Health Sciences, University of Gondar, Gondar, EthiopiaCorrespondence: Ashenafi Kibret Sendekie Tel +251918290894Email ashukib02@yahoo.com; Ashenafi.kibret@uog.edu.etIntroduction: Community pharmacy professionals are among the initial healthcare providers and could play crucial roles in preventing and managing cardiovascular disorders. This study aimed to assess perceptions and involvements of community pharmacy professionals in the prevention and management of cardiovascular disorders in Gondar city and nearby rural towns, Northwest Ethiopia.Methods: A multi-centered cross-sectional survey was conducted on community pharmacy professionals in Gondar city and the nearby rural towns from June to July 2021. Independent sample t-test and one-way ANOVA were used to show mean score differences of pharmacists towards the prevention and management of cardiovascular diseases. A 95% confidence interval with a P-value of < 0.05 in the tests was considered statistically significant.Results: Of the 223 initial samples, 210 completed the survey and resulted in a 94.2% response rate. The average perception and involvement scores of the community pharmacy professionals towards the prevention and treatment of the cardiovascular syndromes were 4.1 and 3.8, respectively. Numerous professionals (> 86%) agreed on weight reductions, alcohol consumption restrictions and physical exercises to decrease cardiovascular risks. Pharmacy professionals recruited from Gondar city had significantly higher mean scores compared with pharmacy professionals involved from rural towns (P < 0.001). A significant difference in mean involvement score was also noted in regarding the numbers of clients serving/day (P = 0.026).Conclusion: Community pharmacy professionals had good perceptions on prevention and management of cardiovascular diseases. However, their level of involvement in measuring weight, blood pressure and glucose level, dispensing equipment for home blood pressure and glucose monitoring and keeping records of patients needs to be encouraged. Professionals might benefit from enhanced training to increase their knowledge and confidence.Keywords: cardiovascular disease, community pharmacists, involvements, perceptions, Ethiopia